التدابير الوقائية في مكافحة الأوبئة بين الفقه الإسلامي والقانون الجزائري _ وباء كورونا أنموذجا _ - قحمص, أم هاني (جامعة الوادي university of eloued, 2023)
إن مسألة الوقاية من الأمراض الوبائية مسألة قديمة حديثة، تثار كلما ظهر وباء يهدد انتشاره الإنسان بشكل مباشر، وهذا بالفعل ما حدث خلال انتشار فيروس كورونا كوفيد_19، الذي دفعنا للقيام بهاته الدراسة المعنونة ب: "التدابير الوقائية في مكافحة الأوبئة بين الفقه الإسلامي والقانون الجزائري _فيروس كورونا أنموذجا_" والتي جاءت لتجيب عن الإشكالية الموالية: ما هي التدابير التي اعتمد عليها الفقه الإسلامي والقانون الجزائري في مكافحة الأوبئة. وقد سعينا من خلال هذه الدراسة إلي تبيين دور وفعالية الفقه الإسلامي في مكافحة الأوبئة وقدرته على التحكم في الأزمان، والسيطرة عليها، وكذا تتبع مجهودات المشرع الجزائري، وتقييمها من خلال مقارنته بما جاء في الفقه الإسلامي، وقد وصلنا في نهاية هذه الدراسة إلى مجموعة من النتائج تتمثل أبرزها في: أن كل من الفقه الإسلامي والقانون الجزائري قد اتفقوا على أن الحجر الصحي والغلق العام وتدابير النظافة والتباعد الإجتماعي ضرورية للحد من انتشار الأوبئة، وأنهم اختلفوا في كيفية تطبيقها. كما توصلنا أيضا إلى أن الفقه الإسلامي كان له فضل السبق والتمييز عن باقي القوانين الوضعية، باعتبار أنه قد عزز هذه التدابير بتدابير أخرى تدخل ضمن ثوابت الدين والعقيدة والمتمثلة في الدعاء والوعد بالشهادة والصبر، والتي تعد ضرورة للحفاظ على الصحة النفسية للإنسان، والتي قد يؤثر تدهورها على صحته الجسدية. - The issue of preventive measures against infectious diseases is an old yet modern issue that arises whenever a direct threat to human spread emerg-es. This was indeed the case during the spread of the COVID-19 corona-virus. It prompted us to conduct a study titled "Preventive Measures in Combating Epidemics: Islamic Jurisprudence and Algerian Law - COVID-19 as a Model." The study aimed to address the following ques-tion: What measures have Islamic jurisprudence and Algerian law adopted in combating epidemics? Through this study, we sought to highlight the role and effectiveness of Islamic jurisprudence in combating epidemics, its ability to manage and control crises, as well as tracking the efforts of Alge-rian legislation and evaluating them by comparing them to Islamic juris-prudence. In conclusion, we reached several results, the most prominent of which are as follows: Both Islamic jurisprudence and Algerian law agree that quarantine, general lockdown, hygiene measures, and social distanc-ing are necessary to limit the spread of a pandemic. However, they differ in the implementation methods. We also found that Islamic jurisprudence has the advantage of reason and distinction from other positive laws, as it reinforces these measures with other measures that fall within the constants of religion and belief. These include supplication, the promise of martyr-dom, patience, which are necessary for maintaining the mental health of individuals, as its deterioration may affect physical health.
شريعة
Keywords: تدابير وقائية، مرض، وباء، فيروس كورونا.; Preventive measures, epidemic, coronavirus,measures.